ANALISIS PENGETAHUAN MASYARAKAT TENTANG PENYAKIT RABIES DI DESA PASSO KECAMATAN BAGUALA KOTA AMBON - Godlife Leklioy; George Tomatala; Isak Siwa (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
Rabies is a highly lethal zoonotic disease and remains a public health problem, especially in endemic areas such as Ambon City. Passo Village, as one of the affected areas, has recorded a number of positive cases of rabies in animals as well as several suspected rabid dog bite victims. This study aims to analyze the level of public knowledge regarding rabies control in Passo Village, Baguala District, Ambon City. The study was conducted using a survey method with a purposive sampling technique on 30 respondents who own pet dogs, with data collected through questionnaires and interviews. Data analysis was conducted using a Likert scale. The results showed that the majority of respondents were of productive age (15–64 years) and had a high school education at the highest level. The average community knowledge score regarding rabies reached 4.07 with a percentage of 82.12%, which is classified as